2017
DOI: 10.1001/jama.2017.4287
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Infective Endocarditis in California and New York State, 1998-2013

Abstract: In California and New York State, the overall standardized incidence of infective endocarditis was stable from 1998 through 2013, with changes in patient characteristics and etiology over this time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
334
10
20

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 282 publications
(387 citation statements)
references
References 26 publications
23
334
10
20
Order By: Relevance
“…The oral formulation of oxymorphone, Opana ® (Purdue), which came to market in 2006, was modified to an abuse deterrent form in 2012, which coincides with when the increase in OPR injection was reported. These findings mirror those found by Toyoda et al [1] characteristics of the formulation that increases the risk of developing IE. This is a common theme in studies regarding IDUaIE and similar questions were left unanswered in the study by Chambers et al [5].…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The oral formulation of oxymorphone, Opana ® (Purdue), which came to market in 2006, was modified to an abuse deterrent form in 2012, which coincides with when the increase in OPR injection was reported. These findings mirror those found by Toyoda et al [1] characteristics of the formulation that increases the risk of developing IE. This is a common theme in studies regarding IDUaIE and similar questions were left unanswered in the study by Chambers et al [5].…”
Section: Resultssupporting
confidence: 90%
“…However, injection drug use (IDU) associated IE (IDUaIE) steadily increased over this period of time [1]. This problem is particularly highlighted in North Carolina where IDUaIE admissions increased twelvefold from 0.2 to 2.7 per 100,000 persons per year from 2010 to 2015.…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of IE among children and adolescents with CHDs was stable in Norway in the period from 1994 to 2016. Similarly, Toyoda et al 23 recently described a stable incidence of IE in the general populations in California and New York State from 1998 to 2013. None of these studies indicated a negative effect of the changes in the guidelines on the incidence of IE.…”
Section: Discussionmentioning
confidence: 74%
“…Toyoda et al 23 recently reported an annual incidence of paediatric IE ranging from 0.3 to 3.3 per 100 000 children and adolescents. The frequency of IE in children without pre-existing heart disease is approximately 0.03 per 10 000 person-years in Norway 2.…”
Section: Discussionmentioning
confidence: 99%
“…The mean age of patients with IE in Europe and the United States was greater than 60 years [3,4]. The fact that a relatively younger age group of IE patients was present in this paper could provide an alternative explanation for the low incidence of stroke as observed in our sample population.…”
Section: Discussionmentioning
confidence: 72%